The atlas of changing South Africa - Christopher, A. J., 1939- (Routledge, 2001)
This book is a comprehensive introduction and detailed analysis of the spatial impact of apartheid in South Africa. The Atlas presents the policy and its impact in visual, spatial forms by including over 70 maps.